2020
DOI: 10.1590/1980-265x-tce-2018-0441
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Nursing Education in Brazil: Perspectives for Primary Health Care

Abstract: Objective: To analyze the limitations, strategies, importance and obstacles in mental health education in undergraduate nursing, focused on the role of nurses in Primary Health Care. Method: An exploratory descriptive study conducted with 103 professors in the mental health area of Bachelor/Postgraduate nursing courses from 89 public Higher Education Institutions in the five regions of Brazil. Results: Only 23.3% (24) of the professors teach mental health classes only in primary health care. Of the sample, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
0
4
0
6
Order By: Relevance
“…Nevertheless, the adoption a broadened and psychosocial perspective to the detriment of the sole study of psychopathologies and symptoms generates challenges and resistance among educators and students who must operate in a new model (29) . The lack of coordination between collective health and mental health disciplines is an obstacle to the training nursing professionals (30) . A study (30) reported some barriers in health institutions (university and health services) that can hinder the teaching of mental health applied to the context of PHC, such as: limited workload, lack of teachers to conduct the practice in PHC scenarios, and resistance of health teams/center managers.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the adoption a broadened and psychosocial perspective to the detriment of the sole study of psychopathologies and symptoms generates challenges and resistance among educators and students who must operate in a new model (29) . The lack of coordination between collective health and mental health disciplines is an obstacle to the training nursing professionals (30) . A study (30) reported some barriers in health institutions (university and health services) that can hinder the teaching of mental health applied to the context of PHC, such as: limited workload, lack of teachers to conduct the practice in PHC scenarios, and resistance of health teams/center managers.…”
Section: Discussionmentioning
confidence: 99%
“…Revelou-se, em estudo realizado sobre a necessidade da formação continuada em saúde mental, em serviço não especializado, que os profissionais não se sentiam capazes de atender às demandas em saúde mental e não costumavam buscar conhecimentos específicos para se informar sobre o tema, por vezes, pela insuficiência da formação no ensino superior, o que demanda estratégias urgentes de enfrentamento direcionadas às necessidades dessa população. 12 Compreende-se que a demanda em saúde mental nem sempre estará presente no momento da chegada da pessoa à unidade, mas poderá ser percebida pelos trabalhadores durante o processo (Lele e Rosa). Sabe-se que o período de internamento pode ser vivenciado pela pessoa de DISCUSSÃO diferentes maneiras e que são diversos os fatores capazes de influenciar negativamente a experiência do internamento, repercutindo na forma como a pessoa percebe esse processo e em como ela é afetada, reverberando, assim, no humor, no comportamento e na interação social.…”
Section: [] Mas Têm Saúdeunclassified
“…Uma investigação em 89 instituições de ensino públicas no Brasil desvelou que somente (24) 23,3% dos docentes conduzem o ensino de saúde mental apenas na atenção primária à saúde com estratégias de visita domiciliar, ações educativas e busca ativa de casos de saúde mental. Essa realidade revela que o ensino de saúde mental ainda está centrado nos cenários de especialidade, o que dificulta que o processo formativo do enfermeiro generalista contemple competências para que este consiga prover cuidados primários em saúde mental, identificar precocemente sujeitos em sofrimento psíquico e atuar no tratamento de quadros psiquiátricos estáveis, na prevenção e promoção da saúde mental (64) .…”
Section: Diluir Os Conteúdos De Enfermagem Psiquiátrica Eunclassified